A new species for the vascular flora of Algeria: Cyperus eragrostis (Cyperaceae) - Bouldjedri, Mohammed; De Belair, Gerard; Mayache, Boualem; Sebti, Mohamed (Hacquetia, 2021)
This study provides a definition and description of Cyperus eragrostis as a new alien species to Algeria and North African flora. This hemicryptophyte, native to the tropical parts of South America, is recorded for the first time in Jijel eco-complex wetlands in North-East Algeria. Applying the standard phytosociological method we studied the stands in which this alien species grows together with other hygrophilous and ruderal species. The present study improves the knowledge of the Algerian flora and completes the information about the distribution of C. eragrostis reported by the available international literature and public herbaria.